2017
DOI: 10.1097/wnr.0000000000000782
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 repressed astrocyte activation following lipopolysaccharide stimulation in vitro and in neonatal rats

Abstract: Vitamin D3 has been reported to be an immunity modulator and high levels of vitamin D3 are correlated with a decreased risk for developing diseases in the central nervous system. Astrocytes are important immune cells and contribute toward inflammation during neurological diseases. The vitamin D receptor has been reported to be expressed in astrocytes; however, the effect of vitamin D3 on astrocyte activation has not been studied. Here, we found that lipopolysaccharide stimulation in astrocytes could enhance th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…In contrast, vitamin D suppressed the expression of proinflammatory cytokines, such as tumor necrosis factor-α, interleukin-1β, and TLR4 in vivo . These results support a function of reactive astrocytes in stimulating the inflammatory response in neurodegeneration and brain injury and a putative role of vitamin D (Jiao et al, 2017).…”
Section: Vitamin D3 In Neurological Disorderssupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, vitamin D suppressed the expression of proinflammatory cytokines, such as tumor necrosis factor-α, interleukin-1β, and TLR4 in vivo . These results support a function of reactive astrocytes in stimulating the inflammatory response in neurodegeneration and brain injury and a putative role of vitamin D (Jiao et al, 2017).…”
Section: Vitamin D3 In Neurological Disorderssupporting
confidence: 73%
“…Astrocytes, which are VDR expressing cells, are important immune cells and contribute to inflammation during neurological disorders. Jiao et al (2017) reported that lipopolysaccharide-stimulated neuroinflammation in astrocytes could enhance the expression of the VDR and Cyp27B1. In contrast, vitamin D suppressed the expression of proinflammatory cytokines, such as tumor necrosis factor-α, interleukin-1β, and TLR4 in vivo .…”
Section: Vitamin D3 In Neurological Disordersmentioning
confidence: 99%
“…We searched for a substance with properties to suppress the expression of inflammatory receptors and any substance that could reduce the damage to the BBB. Interestingly, vitamin D3 has these properties [22,23,45]. In addition, astrocytes express the vitamin D3 receptor VDR [46].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D3 stimulates its receptor, vitamin D receptor (VDR), on all neuronal cells, including astrocytes [20]. Furthermore, vitamin D3 has neuroprotective roles through its influence on the expression of nitric oxide synthase (iNOS), which in turn affects nitric oxide (NO) [20], decreases TLR4 expression on astrocytes [21,22] and reduces BBB damage [23].…”
Section: Introductionmentioning
confidence: 99%
“…The regulatory role of VitD in adaptive immune response also includes an inhibitory effect on DCs maturation and differentiation ( 28 ) and a Foxp3 + Tregs expansion ( 29 ). Direct immunomodulatory effects of VitD on CNS cells such as neural stem cells ( 30 ), astrocytes ( 31 ), and microglial cells ( 32 ) have been recently reported. VitD analogs with similar VitD immunomodulatory attributes but devoid of its side effects such as hypercalcemia and hyperphosphatemia have been developed ( 33 35 ).…”
Section: Introductionmentioning
confidence: 99%